Naproxen (Alone) Vs Tramadol Hydrochloride +Acetaminophen in the Management of Osteoarthritis of the Knee: A 13 Week Prospective Study at Tertiary Care Hospital - Pavani, Batchu; Krishna, Tatinada Ramya; Neha, Thatikonda; Vamsi, Kandimalla Krishna; Kalyan, Voguri Bhanu; Ramesh, Ganipisetti; Gottipati, Satheesh S; Babu, Puttagunta Srinivasa (Indian Journal of Pharmacy Practice)
Aim: The main aim of the study is to assess the effectiveness of Naproxen (Alone) Vs Tramadol Hydrochloride + Acetaminophen in the management of osteoarthritis of the knee. Objectives: To determine and evaluate effectiveness of drugs prescribed, Cost effectiveness analysis. Methodology: The present Prospective, Observational study with 100 subjects were from Orthopaedic department with Osteoarthritis of the knee. The subjects were selected on the basis of inclusion and exclusion criteria. The subjects were followed for every 14 days (2,4,6 weeks) and the severity of the pain was calculated by using Oxford knee score. All statistical analysis was carried out with SPSS software. Results: Paired t-test was calculated for two groups and the result was found to be statistically significant. When compared to Group B (Tramadol Hydrochloride + Acetaminophen), Group A (Naproxen) was found to be highly significant. Conclusion: Naproxen was ranked the most effective individual knee OA treatment for improving both pain and function followed by Tramadol Hydrochloride + Acetaminophen. Group B treatment shows cost effectiveness. Further research is required to investigate the use of these drugs in treating OA of the knee. Hence it is necessary to make awareness to physicians and pharmacists, therefore clinicians should promote the rational use of these drugs in the management of OA of the knee.
Keywords: Osteoarthritis; Effectiveness; Oxford knee Score; Naproxen; Tramadol Hydrochloride + Acetaminophen.